The Influence Of Consumer Testımonıals And The Qualıty Of Goods On Fashıon Purchase Interest In The Shopee Marketplace (Case Study Of Economıcs Students Of PGRI Wıranegara Unıversıty East Java Indonesıa) - Sugeng Pradikto; Nunuk Indarti; Nurus Sobakh; Chusnul Khotimah (Cita Konsultindo Research Center, 2023)
Consumer Testimonials, Quality of Goods, and Purchase Interest.The rapid development of information technology gives rise to a new style in the trading system. The internet has many beneficial uses in various fields, one of which is in the field of buying and selling business. With the internet, everything can be obtained easily, there is no need to go to the mall or to shops, just through the internet you can shop quickly and easily. This has finally triggered the emergence of a new paradigm, namely the presence of an online business (online shopping). The research design in this study uses a quantitative approach with descriptive research methods to determine the effect of consumer testimonials and quality of goods on interest in buying fashion in the shopee marketplace with purposive sampling technique, to determine the number of samples, it is calculated using the slovin formula (Sugiyono, 2011: 37) and obtained a sample of 71 respondents. The data collection tool used in this study was a questionnaire or questionnaire and the results were analyzed using multiple linear regression analysis. The results of the study indicate that partially the two independent variables have a positive and significant effect on purchase intention, it is known that the testimonial variable has a t-count value of 2,922, and the goods quality variable has a t-count value of 3,277 with a t-table value of 1.995. Simultaneously, the two independent variables have a significant effect on purchase intention with a significant value of 0.002 < 0.05 and F count 5,697 > 3,130. It is known in the coefficient of determination test, the value of R square is 0.345, which means that testimonial ang quality product have an effect of 34,5% on interest in buying fashion, while the rest (100% - 34,5% = 65,5%) is explained by reasons - another reason.